Predictors for long-term outcome of pulmonary valve perforation and balloon valvuloplasty in neonates with critical pulmonary valve stenosis or pulmonary valve atresia with intact ventricular septum - Abu-Tair, Tariq; Willershausen, Ines; Friedmann, Melanie; Rubarth, Kai; Weigelt, Annika; Martin, Claudia; Dittrich, Sven; Kampmann, Christoph (Frontiers in Cardiovascular Medicine, 2025)
IntroductionPercutaneous balloon valvuloplasty is the treatment of choice for critical pulmonary valve stenosis (CPS) and pulmonary valve atresia with intact ventricular septum (PA/IVS) if the ventricle has a suitable size. This study aimed to evaluate the long-term outcomes and predictors for surgical intervention and pulmonary valve replacement in patients with CPS or with PA/IVS after PBV, considering different morphological and hemodynamic parameters.MethodsNeonates with PA/IVS or CPS who were admitted to the University Medicine Mainz and University Hospital Erlangen between November 1994 and March 2013 and underwent successful PBV as an initial procedure, with a follow-up of at least 5 years (median 13.1 years), were included. The Z-scores of pulmonary valve diameter, balloon/annulus ratio, number of cusps, and persisting stenosis were analyzed. The endpoint was the need for surgical procedures or valve replacement.ResultsA total of 62 neonates (median age at intervention 5 days) were included. Among them, 15 patients (24.2%) reached the endpoint. The mean time of freedom from surgery differed according to the number of cusps (P < 0.001), pulmonary valve diameter Z-scores (P = 0.04), and degree of persisting stenosis (P = 0.008), but did not differ according to the balloon/annulus ratio (≤1.2 vs. >1.2).ConclusionPulmonary valve perforation and PBV achieved favorable long-term outcomes in neonates with PA/IVS and CPS. A small pulmonary valve diameter, reduced number of cusps, and persisting gradient of >40 mmHg increased the risk for reduced time of freedom from surgical intervention and/or pulmonary valve replacement.